Analysis of recommendations for recipients of COVID-19 cash social assistance financing the ministry of social affairs - Susanto, Erliyan Redy; Rusliyawati, Rusliyawati; Wantoro, Agus; Purnama, Citra Andini; Diasari, Itce (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2022)
In order to solve the problems that exist in the economic aspect due to the COVID-19 pandemic in Indonesia, the government has implemented various programs related to economic recovery. One of these programs is cash social assistance (BST). During the implementation of the social assistance program in various regions, it was reported that the recipients of the program were not properly targeted. Based on the results of a survey from one of the leading universities in Indonesia, it is known that many social assistance programs related to the impact of the COVID-19 pandemic are suspected to have not been in accordance with their designation. Based on this, the research was conducted in Bandar Lampung City. The purpose of this study is to conduct an analysis for recommendations for prospective BST recipients, namely people affected by Covid-19. The method used is profile matching by taking samples in the Jagabaya village, Bandar Lampung City. The criteria used include the work of the head of the family, wife's work, home status, number of dependents and ID cards. Based on the results of an interview with one of the BST officials in Bandar Lampung City, in this study the criteria were grouped into core factors and secondary factors. The results of the research can be used by stakeholders as recommendations for prospective BST recipients in Bandar Lampung City. Based on the results of an interview with one of the BST officials in Bandar Lampung City, in this study the criteria were grouped into core factors and secondary factors. The results of the research can be used by stakeholders as recommendations for prospective BST recipients in Bandar Lampung City. Based on the results of an interview with one of the BST officials in Bandar Lampung City, in this study the criteria were grouped into core factors and secondary factors. The results of the research can be used by stakeholders as recommendations for prospective BST recipients in Bandar Lampung City.